Determination of High Sensitivity C-Reactive Protein in Metabolic Syndrome - Gowdaiah, Prakash Kikkeri; Mamatha, T. R.; Nirgude, Dyaneshwar; Hosamani, Prakash Basappa (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Background: A persons personal risk of having cardiovascular disease and type 2 diabetes mellitus is significantly increased if they have metabolic syndrome. Obesity and type 2 diabetes have both become epidemic in India. Metabolic syndrome is a pro-inflammatory condition characterised by low-grade systemic inflammation. The biomarker C-reactive protein (CRP) is a reliable indicator of persistent systemic inflammation. Higher levels of high sensitivity C-reactive protein (Hs-crp) are linked to metabolic syndrome and its components, and can help predict the development of cardiovascular events in the future. Study objectives: 1) Association of High sensitivity C reactive protein with metabolic syndrome 2)Study of High sensitivity C reactive protein as a surrogate marker of chronic inflammation in the metabolic syndrome Materials and Methods: This cross sectional study included 50 patients with metabolic syndrome aged 18 and up, as well as 50 age and sex matched controls who visited the OPD or were admitted to the Bangalore Medical College medical department wards. The metabolic syndrome was diagnosed using the updated IDF criteria.For the measurement of hs-CRP, blood glucose, and lipid profile, a fasting blood sample was taken.At the same time, the waist circumference, height, and weight were measured.The information was tabulated and analysed. Results: There was a statistically significant difference in values of various demographic parameters such as BMI, waist circumference, blood pressure, and biochemical parameters such as blood sugar and lipid profile between cases and controls. Patients with metabolic syndrome had higher mean value of hs-CRP (8.3±1.04 Vs 1.6±0.79mg/l) with a p value <0.001. Conclusion: When compared to controls, patients with metabolic syndrome had considerably higher levels of hs-CRP, and hs-CRP levels rose linearly with the number of metabolic syndrome components. As a result, in patients with metabolic syndrome, hs-CRP can most likely be utilised as a proxy marker of chronic inflammation.